Women Religious Crossing between Cloister and the World : Nunneries in Europe and the Americas, ca. 1200-1700 - Perez Vidal, Mercedes (Book collections on Project MUSE., 2022)
This book presents a comparative approach to the role of women in religious and monastic life in Europe and the Americas during the medieval and early modern periods. The contributors inquire into differences and similarities, continuities and discontinuities of women?s agency inside and outside the convent. The volume challenges traditional chronological and regional limitations such as those between the Middle Ages and the Modern era and stresses the transatlantic exchange of models between Europe and the Americas.